Thrombospondin-1 at the crossroads of corpus luteum fate decisions. Issue 3 (March 2019) - Farberov, Svetlana; Basavaraja, Raghavendra; Meidan, Rina
Abstract : The multimodular matricellular protein thrombospondin-1 (THBS1) was among the first identified endogenous antiangiogenic molecules. Recent studies have shown THBS1-mediated suppression of angiogenesis and other critical activities for corpus luteum (CL) regression. THBS1 is specifically induced by prostaglandin F2alpha in mature CL undergoing regression, whereas luteinizing signals such as luteinizing hormone and insulin reduced its expression. THBS1 interacts both synergistically and antagonistically with other essential luteal factors, such as fibroblast growth factor 2, transforming growth factor beta1 and serpin family E member 1, to promote vascular instability, apoptosis and matrix remodeling during luteal regression. Expression of THBS1 is also downregulated by pregnancy recognition signals to maintain the CL during early pregnancy. This dynamic pattern of luteal expression, the extensive interactivity with other luteal factors and strong antiangiogenic and proapoptotic activities indicate that THBS1 is a major determinant of CL fate.